THE EFFECT OF THE AQUEOUS PHASE pH AND SALINITY ON THE DEMULSIFICATION EFFICIENCY OF HEAVY OIL FROM UKRAINIAN DEPOSITS - Shyshchak, Maxim; Topilnytskyi, Petro (Science-based technologies, 2026)
The presence of water, mechanical impurities, and salts in oils, especially heavy oils, creates serious problems during oil transportation and processing at refineries. Such compounds contribute to the formation of stable oil emulsions, which requires the use of additional technologies for dehydration, desalination, and oil purification, increases operating costs, and leads to higher energy consumption. Demulsification remains a key process for removing water and salts from crude oil. The effectiveness of demulsification depends on many factors, including the nature and properties of the oil and demulsifier, the concentration of the demulsifier, the type of emulsion formed, the temperature, pH, and the water and salt content in the oil. An analysis of publications and studies has shown that for heavy oils from Ukrainian fields, the influence of many of these factors has hardly been studied. To solve this problem, the study investigated the demulsification process of heavy high-viscosity oil from the Bugruvativske field (Sumy region, Ukraine) using three compositions synthesized by the authors. The compositions are based on commercial demulsifiers of the Dissolvan brand (Clariant, Switzerland). The dependence of the effectiveness of these compositions on the NaCl concentration and pH was established. It was determined that the highest efficiency (93-95%) of the studied compositions, regardless of the type and ratio of components in them, is observed in a neutral environment (pH≈7). Increasing the pH to 10 or decreasing it to 2 significantly reduces the dewatering degree. It has been shown that despite a 1.1-1.3-fold decrease in the dewatering degree, when the salinity of the aqueous phase increases from 10,000 mg/L to 50,000 mg/L, the efficiency of demulsifiers remains at a fairly high level of 70-82%. Demulsifiers with a higher ethylene oxide content are more effective at lower salinity, while those with a higher propylene oxide content showed better results at high NaCl concentrations. It was concluded that all synthesized compositions are effective in a neutral environment and high salinity of the aqueous phase. Different ratios of oxyethylated and oxypropylated components in the compositions and the use of different solvents affect their effectiveness. To ensure the reliability and effectiveness of synthesized demulsifier compositions in industrial applications, future research should focus on understanding the optimization mechanism and more thoroughly investigating synergism in multicomponent systems.